2015
DOI: 10.1186/s40659-015-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro response of date palm (Phoenix dactylifera L.) to K/Na ratio under saline conditions

Abstract: Background Salinity is a serious factor limiting the productivity of agricultural plants. One of the potential problems for plants growing under saline conditions is the inability to up take enough K+. The addition of K+ may considerably improve the salt tolerance of plants grown under salinity. It is assumed that increasing the K+ supply at the root zone can ameliorate the reduction in growth imposed by high salinity. The present study aims to determine whether an increase in the K/Na ratio in the external me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…High salinity stress caused more reduction in the weight of shoot and root (1.392 and 1.160 g) as compared to control plants (2.697 and 2.201 g), respectively. Alkhateeb et al [ 66 ] performed experiments on P. dactylifera under salinity stress and found that growth declined with increasing salinity stress. Excess salinity affects plants severely due to water stress, membrane disorganization, nutritional disorders, ion toxicity, and the expansion and reduction of cell division [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…High salinity stress caused more reduction in the weight of shoot and root (1.392 and 1.160 g) as compared to control plants (2.697 and 2.201 g), respectively. Alkhateeb et al [ 66 ] performed experiments on P. dactylifera under salinity stress and found that growth declined with increasing salinity stress. Excess salinity affects plants severely due to water stress, membrane disorganization, nutritional disorders, ion toxicity, and the expansion and reduction of cell division [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Addition of K + to the salt containing media of date palm has reduced the absorption of Na + and also balanced ions compartmentalization. This improvement in growth is accompanied by a decrease in Na + concentration and an increase in K + concentration in the plant tissues with lower Cl − concentrations in leaves and roots of date palm (Alkhateeb et al, 2015). Some results have revealed the identification of miRNAs that share common biogenesis, structure, and expression features with the miRNAs that have been isolated from other plant species.…”
Section: Introductionmentioning
confidence: 83%
“…This indicated that the expression of the ThMYB13 gene increased the uptake of K + in plants and reduced the accumulation of Na + . It has been increasingly recognized that plant salt tolerance is directly reflected by the ratio of K + /Na + in the cytoplasm; the higher the ratio of K + /Na + , the higher ability of salt tolerance of the plant ( Ma et al, 2011 ; Mishra et al, 2014 ; Alkhateeb et al, 2015 ; Zang et al, 2016 ). These results indicated that ThMYB13 might play an important role in tolerance to salt in transgenic T. hispida plants.…”
Section: Discussionmentioning
confidence: 99%